2016
DOI: 10.1136/heartjnl-2016-309995
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of frailty and sarcopenia in heart failure with preserved ejection fraction

Abstract: Frailty is a clinical state in which there is an increase in an individual's vulnerability for developing increased dependency and/or mortality when exposed to stressors. Frailty is often accompanied by heart failure with preserved ejection fraction (HFpEF), and frailty is likely to affect its clinical features and outcomes. Frail patients with HFpEF are frequently associated with sarcopenia (ie, muscle loss and weakness), which is a major component of the pathophysiology of frailty. Sarcopenia is a systemic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 29 publications
1
50
1
1
Order By: Relevance
“…Moreover, the characteristics of the patients with third tertile plasma BNP appear to be consistent with the characteristics of elderly heart failure patients. [ 30 ] On the other hand, there was no difference in motor FIM at admission between the first and third tertile groups. This is likely due to the patients’ inability to move immediately after hip fracture, irrespective of the presence of heart failure.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, the characteristics of the patients with third tertile plasma BNP appear to be consistent with the characteristics of elderly heart failure patients. [ 30 ] On the other hand, there was no difference in motor FIM at admission between the first and third tertile groups. This is likely due to the patients’ inability to move immediately after hip fracture, irrespective of the presence of heart failure.…”
Section: Discussionmentioning
confidence: 97%
“…An increase in adipose tissue further contributes to increased systemic inflammation and leads to decreased levels of adiponectin . Adiponectin is cardioprotective, and low levels lead to increased myocardial oxidative stress and modulation of intracellular calcium‐handling regulatory proteins .…”
Section: Pathophysiologymentioning
confidence: 99%
“…Sarcopenia can be diagnosed when the changes in body composition and muscular mass decrease cause the muscular strength decline. Studies have found that patients with chronic diseases (such as chronic obstructive pulmonary disease, heart disease, digestive tract cancer, hepatic cirrhosis, diabetes, or chronic renal insufficiency) usually have sarcopenia which will affect the outcome of chronic diseases (3)(4)(5)(6)(7). Recently, the parameters related to the human muscular mass and muscular strength are integrated into many diagnostic criteria for malnutrition (8).…”
Section: Introductionmentioning
confidence: 99%